2022
DOI: 10.1177/08862605221115117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Mentors in Violence Prevention Program: A Process Examination of How Implementation Can Affect Gender-Based Violence Outcomes

Abstract: Gender-based violence is a global public health issue and major human rights concern. It is also a type of violence that is disproportionately experienced by women and girls. This study is the first to examine multiple implementation process (dosage, fidelity, and adaptation) effects on changes in anticipated outcomes of a school-based bystander program targeting gender-based violence, Mentors in Violence Prevention (MVP). Data were collected from two participant groups: mentees (students receiving MVP) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
4
9
0
Order By: Relevance
“…Despite the positive changes observed in mentors' attitudes, no signi cant quanti able impact of the programme was observed for mentees. This is in line with previous evaluations in Scotland and the West Midlands [43,28,32]. Two key drivers in bystander behaviour are perceptions of others' willingness and likeliness to intervene, and leadership skills.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the positive changes observed in mentors' attitudes, no signi cant quanti able impact of the programme was observed for mentees. This is in line with previous evaluations in Scotland and the West Midlands [43,28,32]. Two key drivers in bystander behaviour are perceptions of others' willingness and likeliness to intervene, and leadership skills.…”
Section: Discussionsupporting
confidence: 90%
“…racism, county lines, insults, online abuse). Evaluations of MVP in Scotland [24,43,32], Sweden [27], and the West Midlands [28], have also reported little impact of the programme on gender stereotypes and sexist attitudes. Observations of sessions in Sweden demonstrated that whilst some activities such as the gender box, were reported by students as a fun exercise to discuss what is speci c to boys and girls, there was less discussion about how to challenge gender norms [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, published work utilising the same sample used in this article (Pagani et al, 2022b) examining the implementation of Mentors in Violence Prevention, found no dosage (level of exposure to the program), fidelity (extent to which core components such as gender-based violence and bystander intervention were covered during lessons), or adaptation (extent to which components of the program were adapted) effects. However, the change of Mentors in Violence Prevention's scope to also focus on more general violence (Katz, 2018) could potentially dilute the communication of gender-based violence, essentially making it a tick-box exercise (Pagani et al, 2022b), given that mentors are encouraged to cover this as a core value of the intervention. This could be another example of cultural differences across Scotland and America, where the evaluations conducted in America may have been conducted within schools which were fully supportive of the primary focus being on gender-based violence.…”
Section: Discussionmentioning
confidence: 81%
“…Another potential explanation to consider for the null findings is implementation variation (DeGue et al, 2014;Durlak & DuPre, 2008;Jouriles et al, 2018;Kovalenko et al, 2020;Storer et al, 2016). However, published work utilising the same sample used in this article (Pagani et al, 2022b) examining the implementation of Mentors in Violence Prevention, found no dosage (level of exposure to the program), fidelity (extent to which core components such as gender-based violence and bystander intervention were covered during lessons), or adaptation (extent to which components of the program were adapted) effects. However, the change of Mentors in Violence Prevention's scope to also focus on more general violence (Katz, 2018) could potentially dilute the communication of gender-based violence, essentially making it a tick-box exercise (Pagani et al, 2022b), given that mentors are encouraged to cover this as a core value of the intervention.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation